On measuring the bending strength of septate grass stems1. Issue 1 (1st January 2015) - Robertson, Daniel J.; Smith, Simeon L.; Cook, Douglas D.
Abstract : Premise of the study: Reliable testing methodologies are a fundamental tenet of scientific research. However, very little information is found in the literature explaining how to accurately measure the structural bending strength of plant stems. It was hypothesized that the most commonly employed loading configuration used in bending experiments (placement of loading anvil at an internodal region of the stem or stalk) may significantly alter test results and introduce errors in bending strength measurements of plant stems. Methods: Four types of mechanical tests were performed on bamboo ( Phyllostachys aurea ), giant reed ( Arundo donax ), and maize ( Zea mays ) to investigate how different loading configurations employed during three‐point bending experiments affect test results of septate grass stems and to develop a testing protocol that provides reliable measures of stalk bending strength. Results: Results confirmed the hypothesis that internodal‐loaded three‐point bending test can produce erroneous bending strength measurements. This testing methodology causes plant stems to break prematurely and produces failure types and patterns incongruent with stalks that broke in their natural (in situ) environment. In contrast, a modified test configuration produces natural failure patterns and more accurate measurements of bending strength. Conclusion: Reliable measurements of stalk bending strength can be obtained by maximizing the span length of bending tests and placing the loading anvil at stronger and denser nodal tissues. These results are relevant to ecological and evolutionary plant biomechanics studies as well as agronomic breeding studies focused on measuring plant phenotypes such as stalk lodging strength, or on improving bending strength of septate plant stems.